Understanding novel COVID-19: Its impact on organ failure and risk assessment for diabetic and cancer patients - Dariya, Begum (Cytokine Growth Factor Rev, 2020)
The current pandemic outbreak of COVID-19 originated from Wuhan, China. It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with significant mortality and morbidity rate. The severe risk factors are commonly detected in patients of older age and with medical comorbidities like cancer and diabetes. Scientists and doctors have scrambled to gain knowledge about the novel virus and its pathophysiology in order to discover possible therapeutic regimens and vaccines for COVID-19. The therapeutic strategies like targeting the viral genome emphasize the promising approach to target COVID-19. Additionally, blocking the receptor, ACE2 via the neutralizing antibodies for viral escape that prevents it from entering into the cells provides another therapeutic regimen. In this review article, we have presented the effect of SARS-CoV-2 infection in comorbid patients and discussed organ failure caused by this virus. Based on the data available from the scientific literature and ongoing clinical trials, we have focused on therapeutic strategies. We hope that we would fill the gaps that puzzled the researchers and clinicians with the best of our knowledge collected for the betterment of the patients for the coming future.